Immunogenetics of chronic lymphocytic leukemia - Nikhil Patkar; Nikhil Rabade; Pratibha Amare Kadam; Falguni Mishra; Aditi Muranjan; Prashant Tembhare; Shruti Chaudhary; Swapnali Joshi; Hasmukh Jain; Uma Dangi; Bhausaheb Bagal; Navin Khattry; et al. (Wolters Kluwer Medknow Publications, 2017)
Introduction: Cytogenetic aberrations as well as presence of IGVH mutations are the underlying reason for clinical heterogeneity in Chronic Lymphocytic Leukemia (CLL). The presence of IGVH mutations as well as the predominant gene usage shows geographical variations. However, there is no study from India addressing immunogenetics of CLL. In a first Indian study we document the immunogenetics of CLL in a large tertiary hospital. Methods: We analyzed IGVH mutation status, VH gene usage, cytogenetic abnormalities using FISH, immunophenotyping data and correlated them with standard clinical variables in 84 patients of CLL. Results: Advanced Rai stage (Stage 3/4) was seen in 45% of our patients, where as 13q deletion was the commonest clonal cytogenetic abnormality detected in 48.4% of the cases. IGVH unmutated cases (55.2%) showed higher proportion expressing CD38 and CD49d, a preferential usage for VH1 and VH3 families (55.2%), presentation at an advanced Rai stage (52.8%) as well as more frequent presence of p53 deletions. As compared to the IGVH mutated cases greater proportion of IGVH unmutated patients (70%) required treatment. However, there was no significant difference in the time to treatment between mutated and unmutated cases which can be attributed to relatively short median follow up of 10 months. Conclusion: To summarize, we have seen a higher proportion of IGVH unmutated patients in our cohort (55.2%). The commonly used VH genes in the Indian population are IGVH 2-5, IGVH 1-2 and IGVH 1-69. Longer clinical follow up and a larger cohort is necessary to confirm the prognostic value of IGVH mutation analysis in Indian Patients with CLL.